2007
DOI: 10.2164/jandrol.106.002279
|View full text |Cite
|
Sign up to set email alerts
|

GM1 Dynamics as a Marker for Membrane Changes Associated With the Process of Capacitation in Murine and Bovine Spermatozoa

Abstract: ABSTRACT:We previously showed that in live murine and bovine sperm heads, the ganglioside G M1 localizes to the sterol-rich plasma membrane overlying the acrosome (APM). Labeling G M1 using the pentameric cholera toxin subunit B (CTB) induced a dramatic redistribution of signal from the APM to the sterol-poor postacrosomal plasma membrane (PAPM) upon sperm death. We now show a similar phenomenon in the flagellum where CTB induces G M1 redistribution to sterol-poor membrane subdomains of the annulus and flagell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
64
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 66 publications
11
64
0
Order By: Relevance
“…Incubation of Percoll-washed sperm in an IVF medium caused the redistribution of both lipid raft marker proteins into the more confined region of the apical ridge and the labelling appears as a clustering of the punctuated structures that were observed prior to the incubation (van Gestel et al, 2005a). Similar dynamics were described by other groups (Shadan et al, 2004;Cross, 2004;Selvaraj et al, 2007) Interestingly, it is possible to isolate a detergent resistant membrane (DRM) fraction at 4°C using 0.1% Triton X-100 or similar detergent strength buffers. The non-solubilized membranes floated over a discontinuous density gradient and this floating fraction containing the DRM.…”
Section: Sperm Membrane Microdomainssupporting
confidence: 55%
“…Incubation of Percoll-washed sperm in an IVF medium caused the redistribution of both lipid raft marker proteins into the more confined region of the apical ridge and the labelling appears as a clustering of the punctuated structures that were observed prior to the incubation (van Gestel et al, 2005a). Similar dynamics were described by other groups (Shadan et al, 2004;Cross, 2004;Selvaraj et al, 2007) Interestingly, it is possible to isolate a detergent resistant membrane (DRM) fraction at 4°C using 0.1% Triton X-100 or similar detergent strength buffers. The non-solubilized membranes floated over a discontinuous density gradient and this floating fraction containing the DRM.…”
Section: Sperm Membrane Microdomainssupporting
confidence: 55%
“…Deficient actin polymerization in Tssk6-null sperm Changes in the immunofluorescence pattern of sperm surface proteins during capacitation and acrosome reaction have been described previously (Miranda et al, 2009;Saxena et al, 1986;Primakoff and Myles, 2007;Selvaraj et al, 2007). It has been shown that changes in protein localization are at least in part due to actincytoskeleton dynamics (Saxena et al, 1986;Hernandez-Gonzalez et al, 2000).…”
Section: Tssk6 Localizes To the Sperm Headmentioning
confidence: 80%
“…In the same way as the principal piece, the cytoskeleton associated with PM in the acrosomal region is mainly composed of spectrin/F-actin, but with the difference that it is remodeled during capacitation. During capacitation and AR, proteins associated with PM as well as with membrane lipids compartmentalize in the acrosome region; they are redistributed inside the acrosome or distribute towards the equatorial segment and postacrosomal region as well (Rochwerger & Cuasnicu 1992, Da Ros et al 2004, Selvaraj et al 2007, Tsai et al 2007, Pasten-Hidalgo et al 2008. These molecules in some way are maintained as compartmentalized in the acrosome before capacitation.…”
Section: Discussionmentioning
confidence: 99%